Experimental Study of Fluidization in Two-Phase Flow Fluidized Beds with Various Distributor Plates - Pratumtip, Srilaphun; Eiamsa-ard, Smith; Meeyu, Dr.Visanu (Engineering and Applied Science Research, 2013)
A study behavior of fluidization in two-phase flows, a solid and liquid phase is proposed in this paper. This study provides basic knowledge on designing of fluidization bed system. In the experiments, water represents as a liquid phase and glass bed with diameter of 4 mm and 5 mm as a solid phase. A 1,000 mm height tower bed with diameter of 150 mm is contructed. At the inlet of tower is instructed with 5 different distributor plates, which are distributor plate A, B, C, D and E, respectively (as show in Table 4). From the experimental results was found that the main criterion of the minimum fluidization of distributor plates A and D are given a smaller value of U mf ,Psource and Apbed than plates B, C, and E that mean it is used energy less. The bigger size of solid phase is used more energy to produce the minimum fluidization than the smaller one.